2004
DOI: 10.1183/09031936.04.00135703
|View full text |Cite
|
Sign up to set email alerts
|

Atypical pathogens and respiratory tract infections

Abstract: The atypical respiratory pathogens Chlamydia pneumoniae, Mycoplasma pneumoniae and Legionella pneumophila are now recognised as a significant cause of acute respiratory-tract infections, implicated in community-acquired pneumonia, acute exacerbations of chronic bronchitis, asthma, and less frequently, upper respiratory-tract infections.Chronic infection with C. pneumoniae is common among patients with chronic obstructive pulmonary disease and may also play a role in the natural history of asthma, including exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0
17

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(111 citation statements)
references
References 134 publications
3
91
0
17
Order By: Relevance
“…pneumoniae has consistently been recognized as a common cause of CAP. Between 1% and 22% of CAP cases have been attributed to this pathogen [13][14][15][16]18,34]. Clearly, frequency of acute infection (obtained here based on MIF) among CAP patients correlates well with available epidemiological data.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…pneumoniae has consistently been recognized as a common cause of CAP. Between 1% and 22% of CAP cases have been attributed to this pathogen [13][14][15][16]18,34]. Clearly, frequency of acute infection (obtained here based on MIF) among CAP patients correlates well with available epidemiological data.…”
Section: Discussionsupporting
confidence: 50%
“…In the last two decades, C. pneumoniae has been recognized to play a role in the etiology of CAP worldwide. According to epidemiological studies, C. pneumoniae accounts for 1%-22% of patients suffering from CAP [13][14][15][16]. It has been suggested that this pathogen could play an etiological role for CAP in 6% of pediatric outpatients between 6 months and 12 years of age [17].…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of chronicity and persistence, however, is thought to be involved in the pathogenesis of chronic inflammatory airway diseases, i.e. human asthma and COPD, and even in pulmonary emphysema or lung cancer [2,3,14,19,22,26,50,51,56].…”
Section: Introductionmentioning
confidence: 99%
“…При лечении макролидами следует учитывать возможность удлинения интервала Q-T, соблюдать осто-рожность при сочетании его с эуфиллином. Эффек тивность лечения заболеваний нижних дыхательных путей макро-лидами не вызывает сомнений, однако она должна быть обоснована и для болезней верхних дыхательных путей [6].…”
Section: в помощь врачуunclassified
“…Нередок исход в хронический процесс -пневмоскле-роз, бронхоэктазы. F. Blasi считает хламидии и микоплаз-мы основными возбудителями, влияющими на развитие бронхиальной астмы [6].…”
unclassified